Epistemological analysis of the concept of truth at David Deutsch - حسن, محمود; إبراهيم رزوق (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
The concept of truth constituted the main pillar of epistemology throughout its long history , Philosophers and scientists considered the concept of truth is the main element in the process of cognitive research , The concept of truth was classified as the supreme goal that culminates the process of cognitive research , Therefore, philosophers of science have always sought to base their epistemological doctrines and epistemological theories on the concept of truth as the ultimate goal of all cognitive and scientific research , According to this rule, philosophers of science put forward their epistemological issues within the various fields of cognitive and scientific research in order to reach the cognitive and scientific facts through which they prove their epistemological theories and their epistemological doctrines . The philosopher of science, David Deutsch, is one of the most prominent philosophers of science who researched in the concept of truth , Deutsch considered that knowledge is in a state of constant and continuous development , And the Infinite knowledge transcends the limits of the absolute, enters the threshold of infinity, and extends into the horizon of the infinite to break down the limitations of the absolute and build its infinite cognitive world that is based on the concept of truth that is fully logically realized by the mind , This is far from the limited sensory perception that is restricted to the five senses , This, in turn, contributes to the development of all areas of general human knowledge. Deutsch emphasized that the original source of knowledge is the mind , Thus, knowledge is purely mental and has logical laws, as these laws work to provide mental explanations for scientific and cognitive phenomena in order to reach the cognitive facts , This, in turn, contributes to the development of a holistic view of knowledge, and directly contributes to the epistemological analysis of the concept of truth , So that the knowledge of the changes that occur in all fields of knowledge with its various specializations and its multiple facts is reached , Deutsch shows that knowledge is constantly generated and that there are no definitive explanations for the scientific and cognitive phenomena that exist in the world , All knowledge contains certain percentages of errors, and this is one of the logical reasons that promote the idea of ​​permanent and continuous development and growth of knowledge.